MECHANISM FOR PROVIDING RESTORATIVE JUSTICE IN CRIMINAL CASES AT THE LABUHANBATU DISTRICT ATTORNEY'S OFFICE - Siti Alfadilah; Guntur Rambey (Inspiring Law Journal, 2026)
This study aims to analyze the mechanism of  providing restorative justice in criminal cases at the Labuhanbatu District Attorney's Office, assess the effectiveness of its application in providing justice for perpetrators and victims, and identify obstacles and efforts made in its implementation. This research is motivated by a paradigm shift in the criminal justice system from a retributive approach to a restorative approach that emphasizes the restoration of circumstances, responsibility of the perpetrator, and the restoration of social relations, the research method used is qualitative research with an empirical juridical approach that is descriptive and analytical. The research data was obtained through literature studies and interviews with law enforcement officials at the Labuhanbatu District Attorney's Office. The data obtained is then analyzed qualitatively through the process of data reduction, data presentation, and conclusion drawn.The results of the study show that the mechanism for providing restorative justice is carried out through several stages, namely the assessment of the feasibility of the case, the implementation of penal mediation between the perpetrator and the victim, the exposure of the case in stages within the prosecutor's office, and the issuance of a Decree of Termination of Prosecution (SKP2). The application of restorative justice is considered effective, especially in criminal cases with a low level of seriousness, because it is able to speed up the resolution of cases, provide opportunities for perpetrators to take responsibility for their actions, and restore social relations between perpetrators and victims.However, its implementation still faces obstacles, including low public understanding of the concept  of restorative justice and the limited scope of cases that can be resolved through this mechanism. Therefore, it is necessary to increase legal socialization, involve community leaders in the mediation process, and strengthen the capacity of prosecutors as peace facilitators so that the implementation of restorative justice can run more optimally.